2007
DOI: 10.15517/rbt.v56i3.5690
|View full text |Cite
|
Sign up to set email alerts
|

The impact of local extinction on genetic structure of wild populations of lima beans (Phaseolus lunatus) in the Central Valley of Costa Rica: consequences for the conservation of plant genetic resources

Abstract: Plant populations may experience local extinction and at the same time new populations may appear in nearby suitable locations. Species may also colonize the same site on multiple occasions. Here, we examined the impact of local extinction and recolonization on the genetic structure of wild populations of lima beans (Phaseolus lunatus) in the Central valley of Costa Rica. We compared genetic diversity from the samples taken from the populations before and after extinction at 13 locations using microsatellite m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Also, wild populations of Phaseolus lunatus have a metapopulation behavior (Barrantes et al 2008), implying the existence of extinction and recolonization processes that may affect their genetic structure. It has been noted that the founder effect associated with recolonization increases the differentiation between subpopulations (Wright 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Also, wild populations of Phaseolus lunatus have a metapopulation behavior (Barrantes et al 2008), implying the existence of extinction and recolonization processes that may affect their genetic structure. It has been noted that the founder effect associated with recolonization increases the differentiation between subpopulations (Wright 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that could affect the distribution and genetic differentiation of the wild populations of P. lunatus is their metapopulational behavior (Barrantes et al, 2008). Wright (1977) noted that the founder effect associated with recolonization increases differentiation among subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Selfing is favored by the synchronized maturation of pollen grains and stigma and by their proximity within the flower bud (Webster et al, 1979), but outcrossing rates up to 48% have been reported (Baudoin et al, 1998). Wild populations have metapopulation dynamics (Barrantes et al, 2008) and generate important seed banks in the soil that can remain viable for up to 3 yr after dispersal (Degreef et al, 2002).…”
mentioning
confidence: 99%